Stratigraphic ranking of selected invertebrate fossils: A quantitative approach at different temporal and geographic scales - Abdelhady, Ahmed; Seuß, Barbara; Hassan, Hatem (Palaeontologia Electronica, 2019)
Fossil groups are used for biochronological dating of rocks for decades. This manuscript presents a quantitative approach to appraise and compare the quality of selected taxa as biostratigraphic markers. Based on species occurrence of ammonites, bivalves, and planktic and benthic foraminifers we evaluate the potential of these to rank them quantitatively. The spatiotemporal analyses of occurrence data (species duration, geographic range) were integrated in results of the Unitary Association method, which measures superpositional contradictions in addition to the generation of a number of UAs. The results indicate that Jurassic ammonites have the lowest species duration, and that the majority of species is confined to a single UA-zone. Additionally, ammonites have the lowest numbers of contradicted bio-events. However, planktic foraminifers are more valuable at least in the Cenozoic as they have a high geographic reproducibility and diversity, and higher ISP values. The bivalves and benthic foraminifers both show longer average species durations and more superpositional contradictions per species. Therefore, their biostratigraphic potential is more limited at an interregional scale. The shorter species durations of ammonites and planktic foraminifers in the studied sections can be attributed to their higher extinction rates. As an advantage to simple spatio-temporal analyses, the UA-method can accurately assess the stratigraphic potential of a given taxonomic group. The results obtained herein indicate that the life-habit has direct impact on the species duration and thus, the stratigraphic potential of the fossil groups. Based on the results achieved from this study, an index for ranking fossil groups (Index of Stratigraphic Potential ‘ISP’) is introduced.<br